1974
DOI: 10.1172/jci107750
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Distributions of Ventilation-Perfusion Ratios in Normal Subjects Breathing Air and 100% O2

Abstract: A B S T R A C T A new method has been developed for measuring virtually continuous distributions of ventilation-perfusion ratios (VA/Q) based on the steadystate elimination of six gases of different solubilities. The method is applied here to 12 normal subjects, aged 21-60. In nine, the distributions were compared breathing air and 100% oxygen, while in the remaining three, effects of changes in posture were examined. In four young semirecumbent subjects (ages 21-24) the distributions of blood flow and ventila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
210
1
7

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 444 publications
(239 citation statements)
references
References 17 publications
21
210
1
7
Order By: Relevance
“…Similarly, in two of the three patients with liver disease and arterial hypoxaemia recently reported by EDELL et al [10], the measured Pa,O 2 values were greater than those predicted by MIGET during O 2 breathing. These findings contrast with previously published studies using the MIGET analysis in both normal and patient groups breathing 100% O 2 , in whom the measured Pa,O 2 values were invariably substantially less than those predicted by MIGET [14,21,22]. In our own laboratory, using essentially the same experimental protocol and technical equipment as in the current study, we have never previously observed the measured Pa,O 2 to exceed that predicted by MIGET in a large number of both normal subjects and patients with varying lung disorders when breathing 100% O 2 [23].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Similarly, in two of the three patients with liver disease and arterial hypoxaemia recently reported by EDELL et al [10], the measured Pa,O 2 values were greater than those predicted by MIGET during O 2 breathing. These findings contrast with previously published studies using the MIGET analysis in both normal and patient groups breathing 100% O 2 , in whom the measured Pa,O 2 values were invariably substantially less than those predicted by MIGET [14,21,22]. In our own laboratory, using essentially the same experimental protocol and technical equipment as in the current study, we have never previously observed the measured Pa,O 2 to exceed that predicted by MIGET in a large number of both normal subjects and patients with varying lung disorders when breathing 100% O 2 [23].…”
Section: Discussioncontrasting
confidence: 99%
“…In our own laboratory, using essentially the same experimental protocol and technical equipment as in the current study, we have never previously observed the measured Pa,O 2 to exceed that predicted by MIGET in a large number of both normal subjects and patients with varying lung disorders when breathing 100% O 2 [23]. Indeed, inevitable leaks in the O 2 delivery system, deterioration of the arterial blood samples prior to analysis, and insensitivity of the MIGET analysis to detect physiological postpulmonary shunt should all conspire to produce a positive P-M Pa,O 2 during 100% O 2 breathing [14,21]. Particularly in view of our limited data base, experimental error could explain our observation, the most likely sources being in the actual measurement of Pa,O 2 and/or in the MIGET analysis.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Mathematically this is represented asV A /Q whereV A is the ventilation (volume of gas the reaches the alveoli per unit time) andQ is the perfusion (blood flow rate which reaches the alveoli). Medical literature suggests that typically the ratio should be between 0.2 and 2.1 with a mean of one [7,15,43]. A low ratio means that there is a large amount of excess CO 2 in the lungs, which is representative of hypoventilation (very slow rate of breathing).…”
Section: Ventilation-perfusion Ratiomentioning
confidence: 99%